THE INDEX AND PRESENTATION OF SER‘IYYE RECORDS OF RODOSCUK NUMBERED 1587 - Ayşe ÖZKAN (Fırat University, 2019)
Archival Documents and particularly Court Registers (Şer’iyye Sicilleri) takes important place in the Ottoman History researches. These registers provides valuable data to historians about economic, social, legal and administrative issues of a specified region. In this research Rodoscuk-Tekirdağ court registers which is numbered 1587 and dated to 1640-41 was studied. In this framework working hours and officers of the courts and sorts of documents were analyzed and some statistics were presented based on these archival documents samples. All data extracted from these analyses let us to make new and original evolutions. According to the registers, settlements exist in region compoesed by 27 Muslim and 8 non-Muslim families. Also 38 village name was mentioned. Although Muslims and non-Muslims have been settled in different villages as far as understood from cases both group look owned lands from the other one village. Issues on economy, state cases and family cases mostly seen in the studied registers. Dependently these titles evolutions made in the study based on state and community relations. Also all these outputs are important from the point of view of defining social relations of the era.